2004
DOI: 10.1002/adma.200305742
|View full text |Cite
|
Sign up to set email alerts
|

Aligned Gold Nanorods in Silica Made by Ion Irradiation of Core–Shell Colloidal Particles

Abstract: Colloidal particles with a 14 nm diameter Au core surrounded by a 72 nm thick silica shell have been irradiated with 30 MeV heavy ions. The shell deforms into an oblate ellipsoid, while the core becomes rod‐shaped (aspect ratio up to 9) with the major axis along the beam. Optical extinction measurements show evidence for split plasmon bands, characteristic for anisotropic metal nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
118
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(123 citation statements)
references
References 12 publications
4
118
0
1
Order By: Relevance
“…As the macroscopic stress generated from SHI irradiation in planar constrained films can reach values as large as several hundreds of megapascal, we suggest that mechanism ͑iii͒ can participate to the evolution of the NPs. It should be mentioned that this scenario has already been proposed by Roorda et al 13 to explain the shape change of Au NPs that are confined within a silica shell and assumed to be solid. However, as pointed out by Klaumünzer,16 this indirect mechanism alone is not sufficient to account for the observed deformation of solid NPs; i.e., the metallic NP must actively participate in the deformation process.…”
Section: ͑I͒mentioning
confidence: 96%
See 1 more Smart Citation
“…As the macroscopic stress generated from SHI irradiation in planar constrained films can reach values as large as several hundreds of megapascal, we suggest that mechanism ͑iii͒ can participate to the evolution of the NPs. It should be mentioned that this scenario has already been proposed by Roorda et al 13 to explain the shape change of Au NPs that are confined within a silica shell and assumed to be solid. However, as pointed out by Klaumünzer,16 this indirect mechanism alone is not sufficient to account for the observed deformation of solid NPs; i.e., the metallic NP must actively participate in the deformation process.…”
Section: ͑I͒mentioning
confidence: 96%
“…A detailed investigation of the irradiation-induced deformation has been carried out by Polman's group for NPs with a hybrid structure, viz., a Au-core/silica-shell ͑Au@ SiO 2 ͒ system. [13][14][15] The authors observed that during irradiation with MeV ions ͑4-30 MeV͒, the silica shell turns into an oblate ellipsoidal shape with its main axis perpendicular to the beam direction, while the Au core elongates along the ion beam, provided the silica-shell thickness is large enough ͑Ͼ20 nm͒. This indicates that the deformation of the metal core is somehow related to ion-induced effects in the silica shell.…”
Section: Introductionmentioning
confidence: 99%
“…Freestanding metallic NPs irradiated under comparable conditions do not change shape, demonstrating the embedding a-SiO 2 matrix must have a role in the shape transformation process [8,17]. An unambiguous identification of the atomistic mechanism underlying the transformation remains lacking but a metal NP melt-and-flow process, the latter potentially as a means of relieving in-plane stress within the matrix [8,14,17], is certainly plausible. For this report, we examine the SHII-induced elongation of ten embedded, elemental metal NP systems using a common irradiation condition to enable the identification of subtle, metal-specific differences and demonstrate that the thermodynamic properties of both the matrix and metal are intrinsic to the shape transformation process.…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17] citing selected examples. Freestanding metallic NPs irradiated under comparable conditions do not change shape, demonstrating the embedding a-SiO 2 matrix must have a role in the shape transformation process [8,17]. An unambiguous identification of the atomistic mechanism underlying the transformation remains lacking but a metal NP melt-and-flow process, the latter potentially as a means of relieving in-plane stress within the matrix [8,14,17], is certainly plausible.…”
mentioning
confidence: 99%
See 1 more Smart Citation